Etiology and Epidemiology of Patients Presenting with Liver Disease During Pregnancy (Medical Forum Monthly, 2024)
Objective: We conducted this study to elaborate the etiology and epidemiology of liver diseases presenting during pregnancy.Study Design: It was a prospective, observational study.Place and Duration of Study: This study was conducted in the Department of Gastroenterology, Fatima Memorial Hospital in collaboration with the Department of Obstetrics and Gynaecology from June 2011 –May 2013.Materials and Methods: 73 patients were evaluated. Data was evaluated for quantitative and qualitative variables. Outcome of mother, pregnancy and neonates was also recorded where available.Results: During the study period 73pregnant patients were evaluated for the presence of liver disease giving an incidence of 3.6%. The mean age of the patients was 26.3 + 3.8 (median: 26, range: 16 – 45) years. The patients presented at a mean gestational age of 5.8 + 2.4 (median: 6, range: 1- 9) months. The mean STB and ALT levels were 11.5 + 8.5 (median: 9.3, range: 1.4 – 48) mg/dL and 943.5 + 887.4 (median: 765, range: 13 – 4810) IU/L respectively. The mean duration of jaundice and mean hospital stay were 6.82 + 5.32 (median: 5, range: 2 – 30) days and 5.6 + 2.7 (median: 5, range: 1 – 18) days. Fulminant hepatic failure was seen in 6.8% of the patients. Acute Hepatitis E was the most frequent diagnosis in our population. Maternal deaths were seen in 8.2%, foetal deaths were seen in 12.3% and neonatal deaths in 6.5%.Conclusions: Liver diseases during pregnancy can have multiple causes and may predict poor outcomes for the patients and neonates.